Sistem Pakar Diagnosa Penyakit Pencernaan Pada Manusia Dengan Menggunakan Metode Certainty Factor Berbasis Web - Dani Dani; Samuel Karmadi (Institut Sains dan Teknologi Nasional, 2023)
ABSTRACT A study was conducted to develop a traditional system at Syhifa Medika Public Clinic to overcome the lack of information and time-consuming queues at the clinic, so that people can check their digestive system conditions more easily and efficiently. The developed expert system for diagnosing digestive diseases in humans has succeeded in helping many local people in finding information on digestive diseases and providing time efficiency that is useful for people who live far from the clinic. Therefore, the expert system for diagnosing digestive diseases in humans can be a very useful alternative to improve the current health system. Keywords: Expert System, Digestion, Digestive Disease, Certainty Factor, Web